Hubungan Religiusitas dan Strategi Koping terhahap Tingkat Stres pada Pasien Ca Ovarium yang Menjalani Kemoterapi - Isna Furaida; Tutik Rahayu; Sri Wahyuni (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Ovarian cancer patients undergoing chemotherapy often experience stress due to the side effects of therapy and emotional distress. Religiosity provides a source of inner peace and acceptance of the disease, while coping strategies play a role in how patients deal with the stress they experience. Aims: to determine the relationship between religiosity and coping strategies with stress levels among ovarian cancer patients undergoing chemotherapy. Method: The study employed a descriptive correlational design with a cross-sectional approach. The population included all ovarian cancer patients undergoing chemotherapy totaling 47 patients. The sampling technique used was Total Sampling. Bivariate analysis was performed using the Spearman Rank Correlation test. This research was conducted in the Darussalam and Ma’wa Buildings of Sultan Agung Islamic Hospital Semarang. Result: Based on the Spearman Rank Correlation test on religiosity, the value of r = -0.857 with p-value = 0.000 (p < 0,05) was obtained. This shows a very strong and significant relationshsip between religiosity and stress levels in ovarian cancer patients undergoing chemotherapy. Coping strategies obtained a value of r = -0.810 with p-value = 0.000 (p < 0.05), indicating a very strong and significant relationship between coping strategies and stress levels in ovarian cancer patients undergoing chemotherapy. Conclusion: There is a significant relationship between religiosity and coping strategies with stress levels among ovarian cancer patients undergoing chemotherapy.